Cultural Publics formation, from the integration of the cultural and educational, in the educational mission of the Cultural Community Institutions - Mirtha Numa Rodríguez; Félix Sánchez Rodríguez; Raquel Diéguez Batista (Revista MENDIVE, 2015)
The formation of cultural audiences, though it has been at the core of all contemporary cultural politics, is a task that cultural institutions have failed to address fully even though the investigations carried out on cultural consumption. This article addresses some theoretical considerati ons on which this training is assumed, as a pedagogical process that must develop community cultural institution and suggests some ideas about a Conception .